2013
DOI: 10.1080/09638199.2013.812135
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural productivity differences and credit market imperfections

Abstract: This paper presents a simple model to examine the implication of credit market imperfections when considering the massive variation of agricultural labor productivity across countries. The development of credit markets enables more agents to acquire skills to work in nonagricultural sectors. The expansion of the sectors decreases the labor supply to agriculture as well as increases the supply of modern intermediate inputs to agriculture. Agricultural producers accordingly substitute the relatively cheap interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…However, credit was found to exert a positive impact on agriculture productivity in West Africa, suggesting that better credit market conditions lead to an increase in agriculture value added per worker. This is in line with the findings of Nishida (2014) that the development of credit markets enables more workers to acquire skills to work in non-agriculture sectors. This could also explain the negative coefficient of labour observed in our results.…”
Section: Resultssupporting
confidence: 91%
“…However, credit was found to exert a positive impact on agriculture productivity in West Africa, suggesting that better credit market conditions lead to an increase in agriculture value added per worker. This is in line with the findings of Nishida (2014) that the development of credit markets enables more workers to acquire skills to work in non-agriculture sectors. This could also explain the negative coefficient of labour observed in our results.…”
Section: Resultssupporting
confidence: 91%
“…Baležentis et al (2020) also suggested that policies to improve land productivity, land-use intensity, and the mobility of agricultural labor should be introduced to enhance China's agricultural labor productivity. Agricultural capital or subsidy inputs can improve agricultural production conditions (Nishida, 2014;Garrone et al, 2019), and also accelerate the use of capital to replace labor (Sheng et al, 2016), which in turn accelerates improvements in labor productivity (Caunedo & Keller, 2021). The labor supply can be affected by immigration policies, which not only redistribute labor between agriculture and nonagriculture (Emerick, 2018;Wang & Benjamin, 2019), but also affect the demand for low-skilled workers in labor-intensive agriculture (Devadoss et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%